Detrimental effects of self-administered methamphetamine during pregnancy on offspring development in the rat. (1st August 2017) - Rüedi-Bettschen, Daniela; Platt, Donna M.
Highlights: Prenatal methamphetamine exposure is achieved via maternal iv self-administration. Methamphetamine self-administration has no effect on pregnancy outcome. Achievement of developmental milestones in exposed offspring is delayed. Abstract: Background: Methamphetamine (METH) abuse by pregnant women is a commonly observed phenomenon. While the harmful effects of METH are well described for adults, there is only limited knowledge of the effects of METH use during pregnancy on the developing child. In the present study, we investigated how intraveneous ( iv) METH self-administration throughout pregnancy affected rat dams and their offspring through weaning, compared to controls. Methods: Female rats (n = 16) were trained to self-administer METH iv ; every drug infusion by a dam also resulted in a saline injection to a yoked control (n = 16). When stable levels of self-administration were reached, all females were mated. Daily, 2-h self-administration sessions continued until litters were born. General health and weight was assessed daily in dams and pups. In addition, pups were evaluated for achievement of age-appropriate developmental milestones (i.e., righting reflex, negative geotaxis, pinna detachment, fur appearance, incisor eruption and eye opening). Results: Dams self-administered 2–3 mg/kg/day METH throughout gestation without consequence to dam health or weight gain during pregnancy. All females produced viable litters, and litter size and composition did not differ between saline and METH dams. Similarly, maternal pup-directed behavior was not affected by prior METH self-administration. However, despite a lack of weight difference in pups, METH-exposed pups were significantly delayed in reaching all assessed developmental milestones compared to controls. Conclusion: These results indicate that in utero exposure to moderate METH doses can profoundly and adversely affect offspring development, suggesting that even recreational METH use during pregnancy has potential for harm.